Osmanlı devrinde Yemen’ de mahalli idare (1266- 1337/ 1850- 1918) - Al- Ozair, Abdulkerim (My University, 2000)
1850-1918 Osmanlı döneminde Yemen Vilayeti Mahalli İdareler konusu geçmişte ve günümüzde hakkında kitap yazılmayan konular arasındadır. Bu nedenle, Osmanlıların Büyük İslam Devleti'nin uzantısı mesabesindeki bu dönem büyük önem taşımaktadır. Bu hususları dikkate alarak araştırmamızı biri giriş altı bölüm olarak tamamladık. Girişte Asr-ı Saadet'deki İslam Devleti'nin idari teşkilatı ve Rasulullah (S.A.V)'ın vazetmiş olduğu teşkilatın mükemmelliği, Hulefa-i Raşidin, Emevi, Abbasi ve Osmanlı dönemleri idari teşkilatlarının, özellikle de Yemen Vilayeti idari taksimatının Rasulullah (S.A.V)'in koymuş olduğu sistemden etkilendiği izah edildi. Osmanlı Devleti'nin; Harameyn-i Şerifeyn-i himaye etmek, Portekizlilerin tehditlerini bertaraf edip onları Kızıldeniz gibi İslam denizlerinden kovmak ve Hint Müslümanlarına yardım etmek gibi üstlendiği önemli rollerden bahsedildi. Birinci bölümde Osmanlıların Tanzimat'tan sonra Yemeni Osmanlı vilayeti olarak tesisi ve mahalli idare için öngördüğü esaslar, yeni düzenlemeler neticesinde ortaya çıkan çalkantılar, çalkantıların önlenmesi amacıyla devletin denetim ve idari kurumlarının, önemli şahsiyetlerin ve hatta isyan bayrağını açanların görüşlerine başvurulduğu ve sonuçta Yemen için en iyi idare şeklinin belirlendiği ve Yemen idari taksimat sisteminin günümüze kadar etkisini devam ettiren mükemmel bir hale getirildiği izah edildi. İkinci bölümde Osmanlıların; Yemen vilayeti mahalli idaresinin düzenlenmesi alanında, vilayet, sancak, kaza, nahiye ve köylerde; Vilayet Umum Meclisi, İdare Meclisi ve Belediye Meclisi gibi denetim ve istişari kurumların tanzimi konusunda koymuş oldukları esaslar konu edildi. Vilayet merkezinin, sancak, kaza ve nahiyelerde teşekkül ettirilen idari müesseselerin, yol yapma, demiryolları döşeme, sancaklar ve kazalar arasında telgraf hatları çekme, rüşdiye ve ibtidaiye mektepleri açarak eğitimi vilayet sathına yayma gibi hizmetleri; büyük ölçüde günümüz devletlerinin mahalli idare sistemlerine benzer kanun metinleri ve uygulamalardan yola çıkılarak izah edilmiştir. Üçüncü bölümde Adalet müesseselerinin tanzimi, bölümlere ayrılması, adalet ve istikrarın sağlanması, mazlumun hakkının zalimden alınması, halk arasındaki husumetlerin, belirli zaman içinde çözülmesi ve İkinci Abdülhamid döneminde bu kurumların ıslahı yönünde harcanan çabalar ele alındı. Dördüncü bölümde Yemen Vilayetinde bulunan askeri ve güvenlik teşkilatının, yabancı tehditlerini bertaraf etmede üstlendikleri roller, vilayette meydana gelen isyanları bastırma çabaları, vilayet sathında güvenlik ve istikrarın sağlanmasında gösterdikleri üstün gayretler, vilayet, sancak, kaza ve nahiyelerdeki idarecilerin kamu alacaklarını tahsilde, onlara destek sağlamaları araştırmayı konu edildi. Beşinci bölümde Yemen Vilayetindeki mali teşkilatlar, teşkilatların dakik bir sisteme oturtulması ve bu sayede gelirlerin giderlerin karşılaştırılması, gelirin artış gösterdiği yıllarda Hicaz vilayeti bütçe açığını kapatmak üzere bu vilayete gönderilmesi, ziraat ve el sanatı üretiminin hacmini, üretimin tüketimi karşıladıktan sonra artanın vilayet dışına ihraç edildiği araştırma konuları arasında yer aldı. Altıncı bölümde Yemen Vilayetinin stratejik konumu ve bu konumu nedeniyle İngiltere, Fransa ve İtalya gibi sömürgeci devletlerin Yemen üzerinde kötü emellerine karşı Osmanlı Devleti'nin verdiği savaşlar Taiz Sancağında Osmanlılarla Nevah-i Tisa'da bulunan İngiliz güçleri arasında meydana gelen savaşlar ve bölge halkının bu savaşlara destek vermesi, Kızıldaniz'in Yemen sahillerinde bulunan İngiliz ve İtalyan güçleriyle Osmanlılar arasındaki savaşlar ve Osmanlıların bu savaşlarda sömürgecilere karşı gösterdiği kahramanlıklar araştırmamıza konu edildi. THESIS

Local Administration in Yemen Under the Ottoman Rule 1850 - 1918 The subject of Local Administration in Yemen Under the Ottoman Rule between the years of 1850 - 1918 is among those of which no books were written about it in the past and present times. This is the reason why the period is very important from the viewpoint of extension of The Great Islamic Nation of the Ottomans. Taking these points into consideration we have completed our research in six sections, and a prologue. In the prologue, the administrative organization of the Islamic Nation during the period of Prosperity Century, the excellence of the organization established by our Prophet was explained. It was further noted that the administrative organizations of the Caliphs of Rashid, Ummeyyades, Abbasides and Ottoman periods, and especially of the Yemen State, were effected by the system established by our Prophet. Important roles of the Ottoman Empire in protecting the direct descendants of the Prophet (Harameyn-i Şerifeyn-i) to overcome the threats of the Portuguese and throw them out of the Islamic seas like the Red Sea and to help the Muslims of India were mentioned. In the first section, the principles established by the Ottoman Empire after the Reformation, in arranging Yemen as a state of the Ottoman Empire and the main stages considered for the local administration; the disturbances that arose due to the new arrangements, the fact that the State asked for the thoughts and considerations of the controlling and administrative enterprises, important personages and even those who revolted against the government to overcome these disturbances were mentioned. The result was the fact that the best administrative system for the Yemen state was acquired and it was perfected in a manner to last even to our day. In the second section, the subject was the principles established by the Ottoman Empire in the arranging of the local administration of the Yemen State by forming counseling and controlling institutions like a General Council of the City, Boards of Administration, and the Municipality Councils in cities, provinces, counties, sub districts and villages. The fact that services of the city administration and the other administrative institutions formed in the cities, provinces, counties, sub districts and villages such as building of roads, railroads, forming telegraph lines between the provinces and counties, opening preliminary and high schools of thus spreading the education to the entire State were explained by referring to the similar law texts and applications of the local administrations of the states of our present date. In the third section, the arrangement of the Judiciary systems, its divisions, establishing stability and justice, the obtaining of the rights of the oppressed from the wicked, the solving of the enmities between the people in the course of time, the efforts made to improve these institutions during the reign of Abdulhamit, the Second was considered. The fourth section covered the military and security organisations in the State of Yemen, the role they played in overcoming the threats of the foreigners, the efforts they made in preventing the revolts that occurred in the State, the acts of high level of efforts spent in the establishment of the security and stability in the State, their assistance in collecting the debts owed to the government, in the cities, provinces, counties, sub districts and villages. In the fifth section, the financial organisations in the State, their working in a precise manner, thus enabling the comparison of the incomes and expenses, when the income showed a surplus the sending of the extra money to the State of Hejaz to cover the deficit of this State, the volume of agriculture and the handcraft, the fact that the production met the need and the surplus was exported to the other states was included among the subjects of the research. In the sixth section, the strategically geographic position of the State of Yemen, the wars Ottoman empire had to make against countries like England, France and Italy who had the idea of colonialism in the back of their minds and negative considerations for Yemen, the battles that occurred in the province of Taiz between the Ottoman forces and the English at Nevah-i Tisa, the support the people of the area gave to these battles. The battles between the Ottoman Empire armies with the English and Italian forces on the Red Sea and Yemen shores and the heroic acts of the Ottoman forces during these battles n.were also the subject of this sectio
Keywords: İSLAM TARİHİ; OSMANLI İMPARATORLUĞU-VİLAYETLER; YEMEN_TARİH